Integration of Various Approaches to Religious Studies and Development of Da'wah Science in the Era of Pluralism: A Philosophical Review - Marlida, Siti; Truna, Dody S.; Waluyajati, Raden Roro Sri Rejeki (Hanifiya: Jurnal Studi Agama-Agama, 2026)
This study aims to analyze how the integration of multiple approaches within religious studies can strengthen the development of da‘wah science in the contemporary pluralistic era. The research focuses on key concepts such as integrative–interconnective epistemology, multidisciplinary religious studies, and transformative da‘wah. Using a qualitative philosophical design and a systematic literature review, this study examines major theories in da‘wah, religious pluralism, and the methodological contributions of phenomenology, psychology, anthropology, sociology, and theology. The object of analysis includes the ontological, epistemological, and axiological dimensions linking religious studies and da‘wah. The findings reveal that multidisciplinary integration expands the scope of da‘wah, enriches its scientific methodology, and strengthens its ethical orientation toward universal values, social dialogue, and community empowerment in diverse societies. The study identifies key challenges, including the dominance of normative–textual paradigms, limited multicultural competence among preachers, and insufficient interdisciplinary literacy within da‘wah institutions. This research recommends developing curricula for da‘wah grounded in religious studies, utilizing social research as a basis for planning da‘wah programs, and reinforcing interfaith dialogue as a means to foster social harmony. The study contributes by formulating a transformative and interdisciplinary da‘wah framework that aligns with contemporary pluralistic realities. This research offers an integrative conceptual model for the development of interdisciplinary da‘wah, serves as an academic reference for strengthening religious moderation, and opens new avenues for empirical studies on the implementation of multidimensional da‘wah in pluralistic contexts.